The sexuality by Michel Foucault: a contribution to nursing - Ribeiro, Moneda Oliveira (Revista da Escola de Enfermagem da USP, 1999)
The author develops a reflexion about Foucault conception in relation to the "sexuality dispositive" that has been presented in the book "Microfísica do Poder". She tries to rescue, through this classic literature, a historic and social point of view in the practice of nursing, without missing the actual concepts that depreciate the affection of the personal relations at overvalorize the masculine virilate, converting the pleasure a consumer goods and a goal itself.